Dental Technique Improves Smile and Confidence: A Case Report of Post-Traumatic Discoloured Teeth-30 Month Follow Up (Bangladesh Journal of Dental Research & Education, 2013)
DOI: http://dx.doi.org/10.3329/bjdre.v2i1.15576 Bangladesh Journal of Dental Research & Education Vol.2(1) 2012: 29-30